Evolution of a divinyl chlorophyll-based photosystem in Prochlorococcus - Ito, Hisashi (National Academy of Sciences, 2011)
Acquisition of new photosynthetic pigments has been a crucial process for the evolution of photosynthesis and photosynthetic organisms. In this process, pigment-binding proteins must evolve to fit new pigments. Prochlorococcus is a unique photosynthetic organism that uses divinyl chlorophyll (DVChl) instead of monovinyl chlorophyll. However, cyanobacterial mutants that accumulate DVChl immediately die even under medium-light conditions, suggesting that chlorophyll (Chl)-binding proteins had to evolve to fit to DVChl concurrently with Prochlorococcus evolution. To elucidate the coevolutionary process of Chl and Chl-binding proteins during the establishment of DVChl-based photosystems, we first compared the amino acid sequences of Chl-binding proteins in Prochlorococcus with those in other photosynthetic organisms. Two amino acid residues of the D1 protein, V205 and G282, are conserved in monovinyl chlorophyll-based photosystems; however, in Prochlorococcus, they are substituted with M205 and C282, respectively. According to the solved photosystem II structure, these amino acids are not involved in Chl binding. To mimic Prochlorococcus, V205 was mutated to M205 in the D1 protein from Synechocystis sp. PCC6803 and Synechocystis dvr mutant was transformed with this construct. Although these transgenic cells could not grow under high-light conditions, they acquired light tolerance and grew under medium-light conditions, whereas untransformed dvr mutants could not survive. Substitution of G282 for C282 contributed additional light tolerance, suggesting that the amino acid substitutions in the D1 protein played an essential role in the development of DVChl-based photosystems. Here, we discuss the coevolution of a photosynthetic pigment and its binding protein.